Verification of T descriptor with consolidation size for sub-centimeter non-small cell lung cancer - Goto, Masaki; Kawaguchi, Koji; Fukui, Takayuki; Nakamura, Shota; Hakiri, Shuhei; Ozeki, Naoki; Mori, Shunsuke; Hashimoto, Kumiko; Ito, Toshinari; Yokoi, Kohei (Surgery today (Tokyo, Japan), 2019)
Purpose In the most recent (eighth) edition of the TNM classification, the clinical T descriptor has been adapted to measure the consolidation size of sub-solid lung cancer. Sub-centimeter non-small cell lung cancer (NSCLC) has thereby been subclassified into three groups: Tis, T1mi, and T1a; however, the revision has not been validated well. Thus, we investigated the clinicopathological characteristics and long-term oncological outcomes of sub-centimeter NSCLCs based on the solid size. Methods The subjects of this retrospective review were 99 patients who underwent complete resection for NSCLC with ≤ 1 cm in consolidation size on computed tomography (CT). Survival was reanalyzed after reclassification according to the new TNM classification. Results This cohort consisted of 14 patients with cTis tumors, 18 with cT1mi tumors, and 67 with cT1a tumors. Among the patients with tumors classified as cT1a, two had lymph node metastasis and two had vascular invasion. The cumulative incidences of recurrence at 5 and 10 years were 0% for cTis/cT1mi tumors, and 4.5% and 6.1% for cT1a tumors, respectively. Conclusions There may be pathological and survival differences between cTis/cT1mi tumors and cT1a tumors, but not between cTis tumors and cT1mi tumors.